Tn916 insertional inactivation of multiple genes on the chromosome of Streptococcus mutans GS-5. - Procino, J K (1988)
Streptococcus mutans GS-5 was transformed with the Escherichia coli plasmid pAM150 containing the cloned streptococcal transposon Tn916. Southern blot analyses with the tetracycline-resistant determinant of Tn916 showed that Tn916 was inserted into the chromosome of S. mutans at a variety of different sites. Tn916 insertions resulted in the inactivation of genes that code for various steps in the biosynthesis of several different amino acids. Two auxotrophs which contained a single copy of Tn916 were shown to revert to prototrophy at frequencies of about 10(-8). All of the revertant prototrophs were susceptible to tetracycline, indicating regeneration of the functional gene by excision of Tn916.